Experimental and numerical investigation of steel–ultra-high-performance concrete continuous composite beam behavior. Issue 10 (July 2020) - Wang, Haolei; Sun, Tao; Tang, Chen; Wang, Jiejun
This article proposes a new kind of continuous composite beam that consists of steel box-girder and ultra-high-performance concrete waffle slab. The ultra-high-performance concrete helps increase the ultimate capacity and span of structure while reducing the risk of cracking that occurs with ordinary concrete. In order to investigate the mechanical properties of this new type of composite structure, two scaled specimens were designed and tested. One was a steel–ultra-high-performance concrete continuous composite beam, whereas the other, as a control specimen, was a prestressed steel-concrete continuous composite beam. The test results indicate that the bending capacity of steel–ultra-high-performance concrete continuous composite beam is 1.2 times that of steel-concrete continuous composite beam; the cracking strength of steel–ultra-high-performance concrete continuous composite beam is larger than 20 MPa, much higher than the conventional one; the crack development pattern of steel–ultra-high-performance concrete continuous composite beam has its own characteristics, and the cracks appeared in ultra-high-performance concrete slab dominated by micro-cracks with smaller length are numerous and intensive. A finite element model was developed to predict the behavior of steel–ultra-high-performance concrete continuous composite beam. Comparing the numerical and experimental results indicates that, generally, the numerical model can simulate the structural behavior of steel–ultra-high-performance concrete continuous composite beam reasonably. Based on the numerical model, a series of parameter analyses were performed, which indicate that the strength grade of steel, web, and bottom plate thickness play an important role in improving the bending capacity of steel–ultra-high-performance concrete continuous composite beam; the axial tensile strength of ultra-high-performance concrete, rib, and top plate height of ultra-high-performance concrete slab can enhance the bending capacity to a certain extent.